Clinical and epidemiological profile of dengue in sanitary districts III and VII of Recife - Maria Beatriz Araújo Silva; Katiúscia Araújo de Miranda Lopes; Eucilene Kélita de Lima Batista; Bruna Gabriela Carvalho de Lima; Fábia Monique da Silva; Maria Isabelle Barbosa da Silva Brito (Universidade de Pernambuco, 2019)
Objective: Describe the confirmed cases of dengue in sanitary districts III and VII of Recife-PE in 2015. Methods: Descriptive study that had as data source the Online Notification System of Notification of the Secretary of Health of the municipality of Recife. Data were collected for dengue cases reported from January to December 2015. Results: Sanitary District III: 2,317 confirmed cases, serology examination not performed in 40.44%, prevalent serotype DEN4 (39.40%), 66.63% cases of classical dengue and 62.7% female cases. Sanitary District VII: 4,290 confirmed cases, 57.15% serological exam not performed, DEN4 prevalent serotype (57.15%), 48.46% classic dengue cases and 61.8% female cases. Conclusion: New approaches to disease control, supported by research that points to more effective vector control management and sanitation investments, are recommended.